Seismic vulnerability assessment of masonry arch bridges. (October 2021) - Saygılı, Özden; Lemos, José V.
Abstract: A seismic assessment study of two historical masonry arch bridges, with different geometries and spans, is presented. The seismicity of the two locations was analyzed in order to define the seismic action to be applied. Artificial ground motion records were generated accordingly, and real ground motions were also used. The two numerical models were created with a 3D discrete element code. The accuracy of the deformability of the block models was verified by comparison with a finite element model. In situ measurements of the natural frequencies were available for one of the bridges, providing further means for model calibration. Time domain dynamic analyses were performed with each set of ground motions, allowing an evaluation of damage and failure modes under seismic action. The shorter span bridge was found to withstand the regulatory records with minimum damage. In contrast, the longer span bridge displayed a significant vulnerability to earthquake action. The study shows that rigid block models have the ability to represent effectively the dynamic elastic response of the bridges and can be calibrated by ambient vibration measurements. Furthermore, the discrete element models provide a powerful tool to investigate the nonlinear dynamic response and failure of these structures, which has to be based on a comprehensive set of dynamic records.